Transformable Gel-to-Nanovaccine Enhances Cancer Immunotherapy via Metronomic-Like Immunomodulation and Collagen-Mediated Paracortex Delivery - Jin, Seung Mo (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.